2006
DOI: 10.1358/mf.2006.28.10.1037487
|View full text |Cite
|
Sign up to set email alerts
|

Subacute bloodstream blockade effect by self-contraction of spider silk

et al.

Abstract: The present experiment was designed to test the subacute bloodstream blockade effect of supercontraction of spider silk on the femoral artery of rats. Observation on ligated femoral artery lasted 10 days. Blood flow, systolic/diastolic blood pressure, and oxidatively modified proteins in serum were measured before and after ligation. Meanwhile, histological manifestations of femoral artery at different times were observed by HE stain. We found that blood flow and systolic/diastolic blood pressure of femoral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Data set citation: Zhou et al. (2022). Vertical coupling of gusts in the lower boundary layer during super typhoons and squall lines https://doi.org/10.5281/zenodo.6856704.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Data set citation: Zhou et al. (2022). Vertical coupling of gusts in the lower boundary layer during super typhoons and squall lines https://doi.org/10.5281/zenodo.6856704.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…[37,44,54] Sometimes, one also uses a rotating pattern on a SLM to emulate the spinning object. [38,55] In this kind of experiment, a vortex beam with a given topological charge 𝓁 impinges on this rough diffusing surface. For small scatterers, the diffused light doesn't carry OAM anymore.…”
Section: Diffusion On a Rotating Surfacementioning
confidence: 99%
“…[13,14] Studies have found that MSCs can increase angiogenesis, regulate extracellular matrix (ECM) remodeling, and accelerate wound closure. [15,16] Compared to other kinds of MSCs, adipose-derived mesenchymal stem cells (ADSCs) are widely available and can secrete most of the cytokines related to wound repair. [17] Moreover, the effect of ADSCs therapy is realized through the paracrine effect mediated by ADSCs secretory factors, exosomes.…”
Section: Introductionmentioning
confidence: 99%